Reflection on Electoral Democracy and Peaceful Transfer of Power: The Tanzanian Experience (Tanzania Journal for Population studies and Development, 2019)
This paper revisits the Africa’s electoral democracy trajectories with the focus on Tanzanian experience of electoral democracy and political transitions. It analyses the conduct of electoral democracy and peaceful transfer of power in Tanzania and gauges whether such experiences may be emulated by other countries particularly those facing crises of political transition in Africa. To do so, the paper adopts documentary review method supplemented by hermeneutic techniques as the most feasible and effective methodology best suited for studying a phenomenon using secondary sources. From this analysis, it is evident, then, although the balance sheet on Tanzania’s experience with democratisation over the last two decades or so shows progressive trends; major power transition remains within the confinements of the ruling party, but Tanzanian experience, still, provides some important lessons for other countries can emulate. Notwithstanding such positive trends, the paper recommends for urgent legal and institutional reforms on the mandate and independence electoral management institution and continuous periodic updating of voters for feasible and the regular processes for individuals opportunity to join with their fellows in replacing, or reinstating the government of their country by means of the ballot-box and without to violence.